L’utilizzo di metodi automatici per l’analisi della forma applicati alla ricerca archeologica - Nanni, Loris; Lumini, Alessandra; Toschi, Monica (Archeomatica, 2013)
The classiï¬cation of shape (e.g. piece of potteries, motif identification, hieroglyphics classification...) is a time consuming task for human being, therefore the objective to develop an automated system for shape classification is welcomed for many archaeologists, freeing them from tedious efforts. Moreover, due to the lack of human experts several artifacts are not studied, this problem could be alleviated using automated systems. A main problem of several proposed shape classifiers is that they need a parameters tuning in each different problem. We show that our system based on an ensemble of approaches is able to work in different applications exactly with the same parameters. This is a very useful for practitioners, with little knowledge of pattern recognition, that need a quick method for their shape classification problem. Two case studies are here reported: automatic classification of the several diverse motifs that are used in the pottery of Kamares style (Cretan cultural production between the first half of the 2nd millennium BC); pieces of pottery classification found in the area of the ancient port city of Class (Italy). The matlab code of the proposed system will be available at http://www.dei.unipd.it/wdyn/?IDsezione=3314&IDgruppo_pass=124&preview= as baseline for other researchers.